Retinal response of low myopes during orthokeratology treatment - Queirós, A. (2020)
The aim of this study was to evaluate the changes in retinal activity during orthokeratology (OK) treatment in 20 myopic eyes. Pattern electroretinography (PERG) and visual evoked potential (VEP) were assessed with the RETI-port/scan21 (Roland Consult, Wiesbaden, Germany). Measurements were taken at baseline (BL) and 1 night (1N), 15 nights (15N), 30 nights (30N), and 60 nights (60N) of OK lens wear. Repeated measures analysis of variance (ANOVA) and the Friedman test were used. Twenty eyes (23.20 ± 3.46 years, 70% female) with visual acuity ≤ 0.00 logMAR in post-treatment showed that despite a slight increase in retinal and cortical response amplitude, observed with both PERG and VEP, respectively, immediately after the initial treatment, these differences found were not statistically significant during the 60 days of OK treatment, despite a statistically significant increase in N95 response with PERG. This shows that retinal and cortical visual-related electrical activity is maintained or slightly increased during OK treatment.